Global analysis of common bean multidrug and toxic compound extrusion transporters (PvMATEs): PvMATE8 and pinto bean seed coat darkening - Islam, Nishat S.; Duwadi, Kishor; Chen, Ling; Pajak, Aga; McDowell, Tim; Marsolais, Frédéric; Dhaubhadel, Sangeeta (Frontiers in Plant Science, 2022)
In common bean (Phaseolus vulgaris), postharvest seed coat darkening is an undesirable trait that affects crop value. The increased accumulation of proanthocyanidins in the seed coat results in darker seeds in many market classes of colored beans after harvest. The precursors of proanthocyanidins are synthesized in the cytoplasm, and subsequently, get glycosylated and then transported to the vacuoles where polymerization occurs. Thus, vacuolar transporters play an important role in the accumulation of proanthocyanidins. Here, we report that the common bean genome contains 59 MATE genes (PvMATEs). Phylogenetic analysis of putative PvMATEs with functionally characterized MATEs from other plant species categorized them into substrate-specific clades. Our data demonstrate that a vacuolar transporter PvMATE8 is expressed at a higher level in the pinto bean cultivar CDC Pintium (regular darkening) compared to 1533-15 (slow darkening). PvMATE8 localizes in the vacuolar membrane and rescues the proanthocyanidin deficient (tt12) mutant phenotype in Arabidopsis. Analysis of PA monomers in transgenic seeds together with wild-type and mutants suggests a possible feedback regulation of PA biosynthesis and accumulation. Identification of PvMATE8 will help understand the mechanism of proanthocyanidin accumulation in common bean.